2013
DOI: 10.1097/jom.0b013e31829b27bf
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Knee Injuries Treated in US Emergency Departments

Abstract: Objective To characterize work-related knee injuries treated in U.S. emergency departments (EDs). Methods We characterized work-related knee injuries treated in EDs in 2007 and examined trends from 1998 to 2007 by using the National Electronic Injury Surveillance System—occupational supplement (NEISS-Work). Results In 2007, 184,300 (± 54,000, 95% confidence interval) occupational knee injuries were treated in U.S. EDs, accounting for 5% of the 3.4 (± 0.9) million ED-treated occupational injuries. The ED-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Koska ESAW -luokittelussa ei keskitetysti kerätä tietoa työtapaturman aiheuttamien vammojen hoidosta [3], tietoa Suomessa tai Euroopassa tapahtuneiden työtapaturmien hoidosta ei ole laajamittaisesti saatavilla. Myöskään Yhdysvalloissa ei kerätä keskitetysti tietoa työtapaturman aiheuttamien vammojen hoidosta [7], eikä aiheesta ole kirjoittajien tietämyksen mukaan julkaistu tieteellisiä artikkeleita. Suomessa vuonna 2014 sattuneiden työtapaturmien määrän [2] ja tapaturmien aiheuttamien sairaalahoitojaksojen eli sairaalan tai terveyskeskuksen vuodeosastolla tai päiväkirurgisessa hoidossa hoidettujen potilaiden määrästä [8] voidaan päätellä, että noin 4 % kaikista työtapaturmista aiheuttaa sairaalahoitojaksoja.…”
Section: 32018unclassified
“…Koska ESAW -luokittelussa ei keskitetysti kerätä tietoa työtapaturman aiheuttamien vammojen hoidosta [3], tietoa Suomessa tai Euroopassa tapahtuneiden työtapaturmien hoidosta ei ole laajamittaisesti saatavilla. Myöskään Yhdysvalloissa ei kerätä keskitetysti tietoa työtapaturman aiheuttamien vammojen hoidosta [7], eikä aiheesta ole kirjoittajien tietämyksen mukaan julkaistu tieteellisiä artikkeleita. Suomessa vuonna 2014 sattuneiden työtapaturmien määrän [2] ja tapaturmien aiheuttamien sairaalahoitojaksojen eli sairaalan tai terveyskeskuksen vuodeosastolla tai päiväkirurgisessa hoidossa hoidettujen potilaiden määrästä [8] voidaan päätellä, että noin 4 % kaikista työtapaturmista aiheuttaa sairaalahoitojaksoja.…”
Section: 32018unclassified
“…As examples, a large retrospective cohort study of 12,452 lower limb injuries suffered by police officers found that the knee was the most common site of injury (31% of all lower limb injuries) (Lyons et al, 2021) whilst in general duties officers in particular, the knee was been identified as the leading site of injury overall (Orr et al, 2023). Of concern, research suggests that, together with firefighters, police officers have more days away from work following a knee injury than other US government workers (Chen et al, 2013). Thus, not only are knee injuries common but they have a notable impact on police officers and their agencies.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of individuals employed in agriculture experience a musculoskeletal disorder at some point in their careers [1]. The demand for heavy physical work in agriculture is similar to the requirements of sports and recreational activities [2]. In both instances, the functional effort is mainly associated with jumping and twisting movements.…”
Section: Introduction and Objectivementioning
confidence: 99%